Peran Mediasi CSR (Corporate Social Responsibility) Berbasis CAR (Capital Adequacy Ratio) dan LDR (Loan To Deposit Ratio) Terdapat Profitabilitas pada Bank yang Terdaftar di Bei Tahun 2020-2024. - Wahyu Trisanti; Ati Retna Sari; Supami Wahyu Setiyowati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the effect of Capital Adequacy Ratio (CAR) and Loan-to-Deposit Ratio (LDR) on profitability, with Corporate Social Responsibility (CSR) based on Global Reporting Invitation (GRI) indicators as an intervening variable in banking sector companies. The research method used in this study is a quantitative intervening method using secondary data derived from financial reports for the 2020-2024 period. The sample in this study was 40 banks listed on the Indonesia Stock Exchange using a purposive sampling technique. The data analysis technique used in this study was the Measurement Outset Model, an internal model, and hypothesis testing using SmartPLS. The results indicate that Corporate Social Responsibility (CSR) has a mediating role in the effects of Capital Adequacy Ratio (CAR) and Loan-to-Deposit Ratio (LDR) on profitability. This study recommends CSR (Corporate Social Responsibility) by considering the Capital Adequacy Ratio (CAR) and Loan to Deposit Ratio (LDR) factors because these activities require expenditures or financing within the company. Future researchers can consider analyzing other variables related to CSR (Corporate Social Responsibility) and profitability.